Same Day Sub-tenon’s Triamcinolone and Anti-VEGF Injections in Patients with Macular Edema Secondary to Central Retinal Vein Occlusion - Yamanuha, Justin J.; Flock, Carolyn R. (Archives of Clinical and Medical Case Reports, 2018)
Purpose: Sub-tenon’s or suprachoroidal triamcinolone have been shown to effectively reduce macular edema and extend anti-vascular endothelial factor (anti-VEGF) interval in patients with macular edema from retinal vein occlusions [1, 2]. This single site retrospective review was conducted to determine if this combination treatment could achieve similar benefits and also improve visual acuity in patients treated for central retinal vein occlusion (CRVO). Methods: The Mayo Clinic Institutional Review Board (IRB) granted approval for the retrospective review of patients treated with simultaneous same day anti-VEGF and sub-tenon’s triamcinolone acetonide injections for macular edema secondary to CRVO at the Mayo Clinic Health System in La Crosse, Wisconsin. Patients were excluded if the prior treatment history was unknown or if follow up did not occur after three months. Primary Outcomes: Visual acuity, intraocular pressure, optical coherence tomography (OCT) thickness, and anti-VEGF injection interval were analyzed at treatment day and three months. Results: Four patients treated with simultaneous same day anti-VEGF and sub-tenon’s triamcinolone had reduction in OCT thickness and extended anti-VEGF interval at three months. Visual acuity improved by a mean of one line, but the degree of improvement was not proportional to the degree of OCT thickness reduction. Two of four patients required ongoing topical IOP lowering medications at three months. Conclusions: Simultaneous same day anti-VEGF and sub-tenon’s acetonide injections can reduce macular edema and permit lengthened injection interval. Future research is needed to determine if this combination treatment for CRVO associated macular edema can improve acuity if administered early in the treatment course.